Нові знахідки видів роду Leveillula (Erysiphales) на Правобережжі степу України - Коритнянська, В.Г.; Попова, О.М. (Український ботанічний журнал, 2014)
Приведены сведения о распространении на правобережье
Степи Украины шести видов мучнисторосяных грибов рода
Leveillula G. Arnaud (Erysiphales). Из них два вида — Leveillula
lactucarum Durrieu et Rostam и L. verbasci (Jacz.) Golovin —
отмечены на территории исследуемого региона впервые. New records for six species of powdery mildew fungi of the genus
Leveillula G. Arnaud (Erysiphales) in the Right Bank of Steppe of
Ukraine are presented. Two of the species, Leveillula lactucarum
Durrieu et Rostam and L. verbasci (Jacz.) Golovin, are reported
for the first time in the investigated region.